Severe pulmonary hypertension and reduced right ventricle systolic function associated with maternal mortality in pregnant uncorrected congenital heart diseases. (1st November 2019) - Hartopo, Anggoro B.; Anggrahini, Dyah W.; Nurdiati, Detty S.; Emoto, Noriaki; Dinarti, Lucia K.
Abstract : Background: Pregnant uncorrected congenital heart disease patients, especially those who already developed pulmonary hypertension, have increased risk for maternal mortality. The pulmonary hypertension severity and right ventricle function may be associated with higher maternal mortality. The study aimed to investigate the mortality rate of pregnant uncorrected congenital heart disease and the impact of pulmonary hypertension severity on mortality. Methods: This is the sub study of COngenital HeARt Disease in adult and Pulmonary Hypertension Registry. The data of pregnant uncorrected congenital heart disease patients were analyzed from registry database. The maternal mortality was recorded. The data of demography, clinics, obstetrics, and transthoracic echocardiography were collected. The factors that influenced maternal mortality were analyzed. A statistical significance was determined when p value < 0.05. Results: From 2012 until 2017, there were 78 pregnant congenital heart disease patients. Of them, 56 patients were eligible for analyses. The majority of congenital heart disease was atrial septal defect (91.1%). The maternal mortality rate was 10.7% (6 of 56). Pulmonary hypertension occurred in 48 patients, therefore the maternal mortality rate among congenital heart disease‐pulmonary hypertension with majority of atrial septal defect was 12.5% (6 of 48). Among nonsurvivors, 100% suffered from severe pulmonary hypertension as compared to survivors (56.0%), p  = 0.041. Most nonsurvivors were Eisenmenger syndrome (83.3%), significantly higher compared to survivors (22.0%), p  = 0.006. Nonsurvivors had significantly worsened WHO functional class, reduced right ventricle systolic function, and right heart failure. The modes of maternal death were severe oxygen desaturation (66.7%) and respiratory failure and sepsis (33.3%). Most of the maternal deaths occurred within 24 h postpartum period. Conclusion: Maternal mortality rate among pregnant uncorrected congenital heart disease with majority of atrial septal defect was 10.7% and among congenital heart disease‐pulmonary hypertension with majority of atrial septal defect was 12.5%. Factors related with maternal mortality were severe pulmonary hypertension, Eisenmenger syndrome, and reduced right ventricle systolic function.